Implementasi Program Perlindungan Anak Terpadu Berbasis Masyarakat di Kota Palangka Raya - Mita Sari; Wahyu Wahyu; Bachruddin Ali Achmad (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
The purpose of this study was to find out, explain how the implementation of an integrated community-based child protection program, as well as the factors that support and inhibit integrated community-based child protection programs. This research was conducted at the Department of Population Control and Family Planning, Women's Empowerment, Child Protection in Palangka Raya City using qualitative methods. The results of this study indicate that the Implementation of the Community Based Integrated Child Protection Program (PATBM) in the Department of Population Control and Family Planning, Women's Empowerment, Child Protection in Palangka Raya City includes the integrated community-based child protection program that has been running and on target, a community-based integrated child protection program is useful and accepted in the City of Palangka Raya, during the implementation of an integrated community-based child protection program there has been a decrease in the number of violence, Resources Implementation of integrated community-based child protection programs both in terms of human resources and budget is still lacking and inadequate, integrated community-based child protection program received a good response from the people of Palangka Raya City, and strategy undertaken by the Population Control and Family Planning Office, Women's Empowerment, Child Protection in Palangka Raya City in implementing a community-based integrated child protection program is to carry out socialization and training activities for activists or cadres of Integrated Community Based Child Protection in the City Government Palangka Raya.